Răspuns :
Explicație pas cu pas:
[tex] {19}^{9} \times {2}^{3} = (19 \times 2)^{3} \times {19}^{6} = {38}^{3} \times 19^{6} = (38 \times 19)^{3} \times {19}^{3} [/tex]
[tex] {27}^{7} = {3}^{3 \times 7} = {3}^{21} [/tex]
[tex] {3}^{21 - 7} = {3}^{14} [/tex]
[tex] {100}^{100} \div {4}^{100} = (100 \div 4)^{100} = {25}^{100} = {5}^{200} [/tex]
19^9 · 2^3 = 19^(3·3) · 2^3 = (19^3)^3 · 2^3 = (19^3 · 2^3)^3
27^7 : 3^7 = (3^3)^7 : 3^7 = 3^(3·7) : 3^7 = 3^21 : 3^7 = 3^(21-7) = 3^14
100^100 : 4^100 = (4·25)^100 : 4^100 = 4^100 · 25^100 : 4^100 = 25^100 · (4^100 : 4^100) = 25^100 · 1 = 25^100